Protection of Local Workers in Foreign Diplomatic Missions: A Review of Subramaniam a/l Letchimanan v The United States of America and another appeal [2021] 3 MLJ cdxxxvii - Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (Lexis Nexis Malaysia Sdn Bhd, 2021)
There are many Malaysian workers hired by foreign embassies and consulates all over the country on fixed term contract basis and the question arises whether they are protected against dismissal without just cause or excuse. This issue was recently raised in Subramaniam a/l Letchimanan v The United States of America and another appeal where the appellant was abruptly dismissed from employment after some ten odd years in service as a security guard in the respondent’s embassy in Kuala Lumpur. His claim for reinstatement under s 20(1) of the Industrial Relations Act 19672 (‘IRA’) was only referred by the Minister to the Industrial Court in April 2019, a lapse of some 11 years. In a judicial review application, the High Court had allowed the respondent’s diplomatic immunity claim and hence, held that the appellant’s representations under s 20(3) of the IRA do not fall within the jurisdiction of the Industrial Court. In reversing the decision of the High Court, the Court of Appeal held, inter alia, that it is the Industrial Court and not the High Court which is the proper forum to determine the issue as to whether the dismissal of the workman by the foreign diplomatic mission had absolute immunity from local laws. Against the Court of Appeal’s decision, the respondent had applied for leave to appeal to the Federal Court on the issue, inter alia, whether by virtue of the doctrine of sovereign immunity, the dismissal of staff at the embassy can be heard by the Industrial Court. In light of the above, this article reviews the above decision with special focus on job security of workers employed in foreign embassies and consulates.